SOCIALIZATION OF SALTED EGG MAKING IN TENGAH TANI VILLAGE - Mus Nilamcaya; Dein Iftitah; Dian Novianti; Fitri Dian Perwitasari (Jurnal Abdisci, 2024)
Salted egg is a livestock product technology that has quite a lot of enthusiasts. Tengah Tani Village is only accustomed to processing conventional salted eggs without using herbal ingredients. The purpose of this program is to increase the added value and durability of duck eggs and improve the skills of the people of Tengah Tani village in processing herbal salted eggs. Community service activities: 1. Socialization of joint counseling, 2. The direct practice of making herbal salted eggs. The results of community service activities provide a reasonable response where it is quite enthusiastic about attending a series of activities in groups and individuals, where there are innovations by adding spices that can reduce salt levels and fishy flavors.